2016
DOI: 10.12688/f1000research.8993.1
|View full text |Cite
|
Sign up to set email alerts
|

Blood loss predictive factors and transfusion practice during percutaneous nephrolithotomy of kidney stones: a prospective study

Abstract: Objectives Bleeding is the most common complication of percutaneous nephrolithotomy (PCNL). Injudicious transfusion is frequently performed in current practice, even though it is not always needed. This study aimed to identify the predictive factors of blood loss in the PCNL procedure and evaluate the perioperative transfusion practice. Methods A prospective study of PCNL was randomly performed by two consultants of endo-urology at our institution. The inclusion criteria were adults with kidney pelvic stones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
0
14
1
Order By: Relevance
“…Firtantyo Adi Syahputra et al 2016 showed a mean hematocrit drop 5.20 % in PCNL. 8 No robust study comparing mean hematocrit drop depending on the energy sources are available till now. In our study major complications requiring treatment were bleeding, hydrothorax, urinary extravasation, and urinary leakage.…”
Section: Resultsmentioning
confidence: 99%
“…Firtantyo Adi Syahputra et al 2016 showed a mean hematocrit drop 5.20 % in PCNL. 8 No robust study comparing mean hematocrit drop depending on the energy sources are available till now. In our study major complications requiring treatment were bleeding, hydrothorax, urinary extravasation, and urinary leakage.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, children listed for primary PCNL often have a large and complex stone burden. That may be the reason that the transfusion rate in pediatric series (14-24%) is higher than in adults (7-8%) [29]. Given the smallness and fragility of the pediatric kidneys, and the clearly established association between scope/tract diameter and bleeding [25], mini-PCNL seems the way to go in children.…”
Section: Discussionmentioning
confidence: 99%
“…Access to the renal pelvis through the posterior calyx is known to be the best route [2]. Access should be made as such to avoid vascular injuries, such as injuries to segmental and interlobar arteries [3]. Bleeding is a common complication of PNL.…”
Section: Introductionmentioning
confidence: 99%